Silicon mitigates boron deficiency and toxicity in cotton cultivated in nutrient solution - Pereira de Souza Junior, Jonas [UNESP]; de Mello Prado, Renato [UNESP]; Machado dos Santos Sarah, Marcilene [UNESP]; Felisberto, Guilherme [UNESP] (Wiley, 2019)
Silicon (Si) application, both via foliar application and via roots, may be promising to improve plant growth under different biotic or abiotic stresses. In the present study, we investigated whether application of Si can also mitigate the harmful effects of boron (B)-related nutritional disorders, such as B deficiency, when the application of B is inefficient or insufficient, and B toxicity, when the soil presents high levels of B. This may enable producers to apply Si preventively, if there is a low availability of B in the environment or if B deficiency is induced during the growth season due to a water deficit reducing the plant's B absorption. The objective of this study was to investigate the influence of leaf and root Si application on alleviating the harmful effects of B deficiency and toxicity in cotton. Three experiments were carried out with cotton plants (Gossypium hirsutum cv. Bayer FM910®), using a soilless system. In a first experiment, we determined that highest plant Si concentrations were obtained with application of stabilized sodium and potassium silicate at concentrations of 0.8 g L−1 (foliar) and 0.056 g L−1 (roots). Experiment 2 indicated that the B concentrations in the nutrient solution associated with moderate B deficiency, sufficiency and moderate toxicity were 33.7, 83.6, and 130.5 µM B L−1, respectively. In Experiment 3 we evaluated the effect of optimum Si applications on the physiology and dry weight production of cotton plants subjected to B deficiency, sufficiency, and toxicity. Silicon mitigated the harmful effects of both B deficiency and toxicity by increasing whole-plant biomass production and levels of chlorophyll a, chlorophyll b, and total chlorophyll, and reduced initial and maximum fluorescence, thereby improving the quantum efficiency of photosystem II. Collectively, these results indicate that the greatest benefit of Si in mitigating B deficiency occurred with foliar B application, while Si supplied via the nutrient solution was more effective against B toxicity.
Keywords: beneficial element; Gossypium hirsutum; leaf application; micronutrient; nutritional disorder